2006
DOI: 10.1088/0022-3727/39/17/021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate bias on high-rate synthesis of microcrystalline silicon films using a high-density microwave SiH4/H2plasma

Abstract: In this paper, we demonstrate the effect of dc substrate bias on high-rate deposition of microcrystalline silicon (μc-Si) films by using a high-density microwave plasma source. Film depositions are performed at a high silane concentration of 67% (deposition rate of ∼ 60 Å s−1) with a low substrate temperature of 250 °C. The μc-Si films deposited under appropriate negative dc substrate bias exhibit improved film crystallinity, mass density and reduced defect density along with thinner amorphous silicon incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…This variation in material structure with bias has been previously reported in ECRCVD grown films. [35][36][37] Reduced ion energy 38 along with positive substrate bias has been found to improve Si film crystallinity in PECVD. 39 While negative bias has generally been reported as having a detrimental effect.…”
Section: Discussionmentioning
confidence: 99%
“…This variation in material structure with bias has been previously reported in ECRCVD grown films. [35][36][37] Reduced ion energy 38 along with positive substrate bias has been found to improve Si film crystallinity in PECVD. 39 While negative bias has generally been reported as having a detrimental effect.…”
Section: Discussionmentioning
confidence: 99%
“…12 On the contrary, while using high-density microwave plasma source in which the ion density happens to be much lower than the ECR plasma, improvement in crystallinity has been reported in lc-Si films under appropriate negative dc substrate bias. 13 Hence, the reactivity of ion bombardment has been found unanimous in causing gross modifications on the network leading to poly-and microcrystalline structure. In RF-PECVD with moderate power applied to the plasma, negative substrate bias happens to be effective in obtaining an ordered network structure and relatively smooth surface morphology because of further reduced ion density present therein.…”
Section: Discussionmentioning
confidence: 99%
“…11 In case of using direct current (dc) substrate bias, some report demonstrates that positive bias improves the crystallinity while the negative bias damages the material quality as well as the surface in ECR plasma CVD. 12 Using microwave CVD (MWCVD) 13 or RF magnetron sputtering, 14 on the contrary, it has been reported that the crystallinity progresses under adequate negative substrate bias itself whereas higher bias deteriorates the film quality. 15 Although H 2 -dilution to SiH 4 is the most popular way for obtaining nanocrystallization in Si network, [16][17][18] inert gas dilution, e.g., by Ar or He 19-21 has come up as competent alternative, providing a reasonably better throughput and enabling low-temperature deposition, altogether facilitating on issues related to commercial utilization in devices.…”
Section: Introductionmentioning
confidence: 99%
“…In order to deposit high‐quality µc‐Si:H films, researchers employed the substrate bias ( V b ) during the PECVD process to investigate whether the V b can improve the quality of the µc‐Si:H films. Jia et al 11, 12 reported that the negative substrate bias could improve the crystallinity of the deposited Si films. Kosku et al 13 and Johnson et al 14 both reported similar results.…”
Section: Introductionmentioning
confidence: 99%